Buletin Peternakan : PENGARUH FORTIFIKASI NANOPARTIKEL KALSIUM LAKTAT KERABANG TELUR TERHADAP SIFAT KIMIA DAN FISIK BAKSO AYAM - Agus Hadi Prayitno (Peternakan UGM, 2016)
The experiment was conducted to analysis the effect of nanoparticle eggshell calcium lactate fortification on chemical and physical properties of chicken meatballs. The materials were chicken meat, filler, spices, salt, eggshell calcium and nanoparticle calcium lactate. Fortification level of eggshell calcium and nanoparticle calcium lactate on making meatballs was 0.3% of the total meatball dough. Each treatment consisted of five replications